Federal Institutions and Strategic Policy Responses to COVID-19 Pandemic - Shvetsova, Olga; VanDusky-Allen, Julie; Zhirnov, Andrei; Adeel, Abdul Basit; Catalano, Michael; Catalano, Olivia; Giannelli, Frank; Muftuoglu, Ezgi; Rosenberg, Dina; Sezgin, Mehmet Halit; Zhao, Tianyi (Frontiers in Political Science, 2021)
This essay examines the policy response of the federal and regional governments in federations to the COVID-19 crisis. We theorize that the COVID-19 policy response in federations is an outcome of strategic interaction among the federal and regional incumbents in the shadow of their varying accountability for health and the repercussions from the disruptive consequences of public health measures. Using the data from the COVID-19 Public Health Protective Policy Index Project, we study how the variables suggested by our theory correlate with the overall stringency of public health measures in federations as well as the contribution of the federal government to the making of these policies. Our results suggest that the public health measures taken in federations are at least as stringent as those in non-federations, and there is a cluster of federations on which a bulk of crisis policy making is carried by subnational governments. We find that the contribution of the federal government is, on average, higher in parliamentary systems; it appears to decline with the proximity of the next election in presidential republics, and to increase with the fragmentation of the legislative party system in parliamentary systems. Our analysis also suggests that when the federal government carries a significant share of responsibility for healthcare provision, it also tends to play a higher role in taking non-medical steps in response to the pandemic.